2011
DOI: 10.1667/rr2388.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Urinary Biomarkers from X-Irradiated Mice Using NMR Spectroscopy

Abstract: In a major radiological event, rapid screening of radiation-exposed individuals for possible medical intervention is critical. Here we suggest a high-throughput, non-invasive approach to identify radiation biomarkers in urine and demonstrate a proof of principle in mice. Mice were whole-body irradiated (8 Gy X rays), and urine samples were collected from both irradiated and control mice for 7 days after exposure. (1)H nuclear magnetic resonance (NMR) spectra of all the urine samples were acquired on a spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Recently, NMR has been used to identify small molecule metabolites as biomarkers in mouse urine after exposure to 8 Gy wholebody X rays. Changes in these biomarkers were detected on the first day after irradiation, and typically reached their maximum on the third and fourth days after irradiation (24). In this study, the biomarker was temporally dependent, suggesting this biomarker is useful only at certain times following irradiation.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, NMR has been used to identify small molecule metabolites as biomarkers in mouse urine after exposure to 8 Gy wholebody X rays. Changes in these biomarkers were detected on the first day after irradiation, and typically reached their maximum on the third and fourth days after irradiation (24). In this study, the biomarker was temporally dependent, suggesting this biomarker is useful only at certain times following irradiation.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we expand upon earlier published observations of that have reported on the urinary and serum response of the mouse (Amendola et al 2006; Lee et al 2007; Tyburski et al 2008; 2009; Ossetrova et al 2010; Partridge et al 2010; Chen et al 2011) and rat(Randic & Supek 1961; Porciani et al 2001; Lanz et al 2009; Johnson et al 2011; Tang et al 2013; Zhang et al 2014) to γ radiation exposures. Using Ultra-Performance ® liquid chromatography (UPLC) in conjunction with time-of-flight mass spectrometry (TOFMS), we analyzed urine collected from rats prior to and at four time points after exposure to six different doses of gamma radiation ranging from 0.5 to 10 Gy at high dose rate.…”
Section: Introductionmentioning
confidence: 58%
“…While cytogenetics remains the gold standard for biological dosimetry and refinement of dose and potential future cancer risk, metabolomics can provide a first assessment (triage) of exposed individuals. Metabolomics has been used with success in the past to identify biomarkers of radiation exposure in easily accessible biofluids, i.e., urine, in animal models such as mice (4, 19, 20, 25), rats (17, 26) and nonhuman primates (16). In this study we extended the metabolomics approach to urine from humans exposed to TBI that was used as a precursor to HSCT.…”
Section: Discussionmentioning
confidence: 99%